Pengaruh Aromaterapi Peppermint Untuk Mengurangi Mual Muntah Pada Kehamilan Di Puskesmas Pal Tiga Pontianak Tahun 2025: Therecia Wijayanti, Marice, Efrosiana Ludofika Kalista, Asmaurina Pramulya - Therecia Wijayanti; Marice Marice; Efrosiana Ludofika Kalista; Asmaurina Pramulya (STIKes Persada Husada Indonesia, 2025)
Nausea and vomiting during pregnancy is a major problem that occurs in early pregnancy. This condition causes discomfort in the mother and requires treatment to overcome nausea and vomiting. Peppermint aromatherapy is a safe and effective therapy that can be used to treat nausea and vomiting in pregnant women. Peppermint leaves contain essential oils, namely menthol, which has the potential to facilitate the digestive system and can relieve stomach cramps or mild anesthetics and contain carminative and antispasmodic effects that work in the small intestine in the gastrointestinal tract that can overcome or eliminate nausea and vomiting. The purpose of this study is to analyze the effectiveness of peppermint aromatherapy on reducing the frequency of nausea and vomiting in pregnant women. This type of research is a Pre-Experimental study with a One-Group Pretest-Posttest Design approach. The population of this study was pregnant women at the Pal Lima Community Health Center, from January to June 2025, totaling 238 people. The sampling technique used was purposive sampling, which is sampling based on the researcher's considerations that determine special characteristics that are in accordance with the research objectives so that they can answer the research problems. The results of the study were obtained using the Wilcoxon statistical test, where the results showed that Ha was accepted and Ho was rejected, meaning that there was an effect of giving peppermint aromatherapy on reducing the frequency of nausea and vomiting in pregnant women.